Comparison of laboratory and "on-court" endurance testing in tennis - Smekal, G.; Pokan, R.; von Duvillard, S. P.; Baron, R.; Tschan, H.; Bachl, N. (International Journal of Sports Medicine, 2000)
Treadmill testing (TT) commonly used in endurance testing is often not sport-specific. Therefore a field test (FT) for tennis players was developed. The purpose was 1) to compare metabolic and cardiorespiratory response between TT and FT and 2) to assess tennis stroke ratings during FT. In both tests ventilatory variables (VO2, VE, VT, Bf, VE x VO2(-1)), heart rate (HR), and lactate (LA) were measured. For both tests an "individual anaerobic threshold" (IAT) was calculated. The comparison of TT and FT yielded significant differences in cardiorespiratory and metabolic response. LA and VE were significantly higher in TT compared to FT at VO2 of 35, 40, and 45 ml x kg(-1) x min(-1). There were statistical differences between IAT resulting from both tests (TT vs. FT): HR (165+/-16, 175+/-11, p<0.001), VO2 (44.4+/-4.3, 47.8+/-4.8, p<0.05), LA (3.1+/-0.5, 2.5+/-0.4, p < 0.001), VE (97.0+/-15.6, 89.1+/-14.9, p < 0.05), VT (2.66+/-0.34, 2.34+/-0.47, p<0.05), VE/VO2 (27.9+/-3.9, 23.9+/-2.9, p<0.01). High correlation was found between stroke ratings and the national ranking of the players. We concluded that 1) metabolic, ventilatory, and cardiorespiratory demands of TT vs. FT were (semi)sport-specific and significantly different and 2) that the stroke rating in our study was a good predictor for tournament performance (r = 0.94). This type of stroke rating can be implemented in a FT